The role of oxidative biomarkers in feline pan- leukopenia - Khoshvaghti, A; Nojaba, E (Journal of the Hellenic Veterinary Medical Society, 2022)
Feline Pan-leukopenia is an important deadly gastrointestinal disease of cats. It is mostly prevalent in kittens with declining maternal antibodies as well as unvaccinated cats. Vitamin D and E, glutathione peroxidase and superoxide dismutase are essential enzymatic and non-enzymatic components of defensive system involve in defending the body against oxidative radicals. Malondialdehyde is a reliable commonly used marker of overall lipid peroxidation level showing the presence of oxidative stress. Measurement of the total serum antioxidant capacity seems to represent a suitable biochemical parameter for evaluating the overall antioxidant status resulting from antioxidant intake or production, and their consumption by the increasing levels of oxidative stress. The purpose of this study was to investigate the changes in serum levels of Vitamins D and E, glutathione peroxidase, superoxide dismutase, total antioxidant capacity and malondialdehyde in cats infected with pan-leukopenia virus. Ten Persian male cats with clinical and laboratory symptoms of pan-leukopenia (n=10) and ten healthy Persian male cats (n=10) with a mean age of 6±2 months (minimum and maximum age were 3 and 8 months respectively) were selected. Superoxide dismutase, total antioxidant, malondialdehyde and glutathione peroxidase levels were assayed by ELISA, and vitamin E and D were measured by chromatography methods. There were no statistically significant differences between the mean serum levels of vitamin E, superoxide dismutase and total antioxidant in healthy cats and those with feline pan leukopenia infection (P>0.05), while a statistically significant decrease in glutathione peroxidase and vitamin D levels, and an increase in malondialdehyde level were observed (P<0.05). A condition of oxidative stress appears in feline pan-leukopenia, possibly associated with the virus infection. This oxidative stress may play a role in prevention/treatment of feline panleukopenia.